Study on Deformation Law of Subway Construction under Passing Existing Line in Short Distance - Cong-Shuang Luo; Yi-Hong Cheng; Zhe Bai; Tong Shen; Xu-Yang Wu; Qing-Guo Wang (Advances in Civil Engineering)
With the large-scale development and utilization of underground space projects, the subway-led Rail Transit Project is developing vigorously, and the safety and stability of subway under passing existing projects have become a key issue for the future. In this paper, the deformation law of subway tunnel under the existing track is studied by using the method of ROCSCIENCE software and field measurement, which is based on the construction of a new double-tunnel shield-driven subway tunnel under the existing city of pile rapid track project. In the crossing area, the distance between the top of the tunnel and the pile foundation is 6.2 m and the distance between the tunnel and the existing track surface is 19.6 m. It is required that the settlement of track caused by the new tunnel construction should not exceed 2 mm. The results show that the settlement of the existing track is greatly influenced by the new tunnel without reinforcement and grouting, and the maximum settlement is more than 9.92 mm. The settlement of the existing track can be controlled to 1.93 mm by adjusting the construction parameters of the shield machine and grouting reinforcement at different stages during construction.